Childhood interpersonal violence and adult alcohol, cannabis, and tobacco use disorders: variation by race/ethnicity?. Issue 9 (9th January 2018) - Meyers, Jacquelyn L.; Sartor, Carolyn E.; Werner, Kimberly B.; Koenen, Karestan C.; Grant, Bridget F.; Hasin, Deborah
Abstract: Background: Exposure to child maltreatment has been shown to increase lifetime risk for substance use disorders (SUD). However, this has not been systematically examined among race/ethnic groups, for whom rates of exposure to assaultive violence and SUD differ. This study examined variation by race/ethnicity and gender in associations of alcohol (AUD), cannabis (CUD), and tobacco (TUD) use disorders with three types of childhood interpersonal violence (cIPV): physical abuse, sexual abuse, and witnessing parental violence. Method: Data from the National Epidemiologic Survey of Alcohol-Related Conditions-III (N: 36 309), a US nationally representative sample, was utilized to examine associations of DSM-5 AUD, CUD and TUD with cIPV among men and women of five racial/ethnic groups. Models were adjusted for additional risk factors (e.g. parental substance use problems, participant's co-occurring SUD). Results: Independent contributions of childhood physical and sexual abuse to AUD, CUD, and TUD, and of witnessing parental violence to AUD and TUD were observed. Associations of cIPV and SUD were relatively similar across race/ethnicity and gender [Odds Ratios (ORs) ranged from 1.1 to 1.9], although associations of physical abuse with AUD and TUD were greater among males, associations of parental violence and AUD were greater among females, and associations of parental violence with AUD were greater among Hispanic women and American Indian men. Conclusions: Given the paucity of research in this area, and the potential identification of modifiable risk factors to reduce the impact of childhood interpersonal violence on SUDs, further research and consideration of tailoring prevention and intervention efforts to different populations are warranted.